Spark plug
The spark plug design addresses durability issues in high-compression engines by using a specific alloy composition and joint configuration to maintain the integrity of precious metal chips, ensuring extended engine life.
Patent Information
- Application Number
- JP2021148030
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-30
- Filing Date
- 2021-09-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-09-10
AI Technical Summary
Spark plugs using IRRH alloy require further durability improvements due to increased energy demands from high-compression engines, particularly in high EGR engines.
A spark plug design incorporating a discharge portion with a molten joint of a central electrode mother material containing Ni, Cr, Fe, and precious metal chips made of Ir, Rh, and Ta, with specific hardness formulas (F1 and F2) to ensure adequate hardness and durability.
The spark plug design enhances durability by maintaining the integrity of the precious metal chips, preventing their detachment even after extended engine use, thereby improving the longevity and reliability of the spark plug.
Smart Images

Figure 0007622594000001 
Figure 0007622594000002 
Figure 0007622594000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to spark plugs. [Background technology]
[0002] Conventionally, there is a spark plug that uses an IrRh alloy, in which 3 to 30 wt% of Rh (rhodium) is added to Ir (iridium), for the electrode member of the discharge part. Such a spark plug has excellent high-temperature heat resistance and can improve wear resistance at the same time. Aiming to further improve wear resistance, a spark plug described in the following Patent Document 1 has been proposed. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-110114 A Summary of the Invention [Problem to be solved by the invention]
[0004] Patent Document 1 discloses a spark plug in which an electrode member in which at least one of Ta (tantalum) and Nb (niobium) is added in a total amount of 0.3 to 7.5 wt % to an IrRh alloy is provided in a discharge portion.
[0005] In engines with harsh ignition environments, such as high EGR engines, the energy of the ignition coil is increased due to higher combustion compression and higher compression, so the spark plugs also require greater durability.
[0006] The present disclosure has an object to provide a spark plug having improved durability when an IrRh alloy is used for the electrode member.The present disclosure has an object to provide a spark plug having improved durability when an IrPt alloy is used for the electrode member. [Means for solving the problem]
[0007] The present disclosure relates to a spark plug, the spark plug including a discharge portion which discharges when a voltage is applied thereto, a center electrode base material (13a) and a precious metal tip (15) are fusion-joined in the discharge portion, and a fusion portion (31, 32) is formed at the fusion-joined portion, the center electrode base material contains Ni, Cr, and Fe, the precious metal tip contains Ir, Rh, and Ta, and an average Vickers hardness Y of the fusion portion is expressed by formula (f1) using a component ratio α based on a mass percentage concentration of Ir and a component ratio β based on a mass percentage concentration of Ta, Y=113.6+5.1α+62.9β (f1) The molten part contains Ir and Ta so that Y≧330.
[0008] The present disclosure relates to a spark plug, the spark plug including a discharge portion which discharges when a voltage is applied thereto, a center electrode base material (13a) and a precious metal tip (15) are fusion-joined in the discharge portion, and a fusion portion (31, 32) is formed at the fusion-joined portion, the center electrode base material contains Ni, Cr, and Fe, the precious metal tip contains Ir, Pt, and Ta, and an average Vickers hardness Y of the fusion portion is expressed by formula (f2) using a component ratio α based on a mass percentage concentration of Ir and a component ratio β based on a mass percentage concentration of Ta, Y=111.1+4.8α+91.7β (f2) The molten portion contains Ir and Ta so that Y≧310.
[0009] According to the present disclosure, by adjusting the Ir and Ta contained in the fusion zone, the hardness of the fusion zone can be ensured and the durability of the spark plug can be improved. Effect of the Invention
[0010] According to the present disclosure, it is possible to provide a spark plug having improved durability when an IrRh alloy is used for the electrode member. According to the present disclosure, it is possible to provide a spark plug having improved durability when an IrPt alloy is used for the electrode member. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a half cross-sectional view of a spark plug. [Diagram 2] FIG. 2 is a partially enlarged view of FIG. [Diagram 3] FIG. 3 is a diagram for explaining an electrode member and a fusion zone. [Figure 4] FIG. 4 is a diagram for explaining the relationship between the molten zone components, the molten zone hardness, and the durability. [Diagram 5] FIG. 5 is a diagram for explaining the relationship between the ratio of Ta and Ir and the hardness in the fusion zone. [Figure 6] FIG. 6 is a diagram for explaining the length of the fusion zone. [Figure 7] FIG. 7 is a diagram for explaining an electrode member and a fusion zone. [Figure 8] FIG. 8 is a diagram for explaining the relationship between the molten zone components, the molten zone hardness, and the durability. [Figure 9] FIG. 9 is a diagram for explaining the relationship between the ratio of Ta and Ir and the hardness in the fusion zone. [Figure 10] FIG. 10 is a diagram for explaining the fusion zone length. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment will be described with reference to the accompanying drawings. In order to facilitate understanding of the description, the same components in each drawing are denoted by the same reference numerals as much as possible, and duplicated description will be omitted.
[0013] 1, the spark plug 10 includes a housing 11. The housing 11 is cylindrical and made of a metal material such as iron. A threaded portion 11a is formed on the outer periphery of the lower part of the housing 11.
[0014] A lower end of a cylindrical insulator 12 is coaxially inserted inside the housing 11. The insulator 12 is made of an insulating material such as alumina. An upper end 11b of the housing 11 is crimped to the insulator 12, so that the housing 11 and the insulator 12 are joined together. A through hole 12a is provided at the lower end, which is one end of the insulator 12. A center electrode 13, which is an electrode for a spark plug, is inserted and held in the through hole 12a.
[0015] The center electrode 13 is formed in a cylindrical shape using a Ni alloy having excellent heat resistance as a base material. Specifically, the inner material of the center electrode 13 is formed of copper, and the outer material is formed of a Ni (nickel)-based alloy. A tip portion 13a of the center electrode 13 is exposed from the lower end of the lower part of the insulator 12.
[0016] A ground electrode 14 is disposed at a position facing the tip portion 13a of the center electrode 13, and extends in a curved manner integrally with the lower end surface of the housing 11. The ground electrode 14 is also made of a Ni-based alloy.
[0017] 2, the tip portion 13a of the center electrode 13 and the opposing tip portion 14a of the ground electrode 14 form the discharge portion of the spark plug 10. Precious metal tips 15 and 16 are attached to the tip portion 13a of the center electrode 13 and the tip portion 14a of the ground electrode 14, respectively.
[0018] The precious metal tips 15 and 16 are joined to the tip portions 13a and 14a, respectively, by a joining process such as laser welding or resistance welding. The tip portions 13a and 14a correspond to the center electrode base material. In Fig. 2, fusion zones 31 and 32 are formed at the portion where the precious metal tip 15 and the tip portion 13a are joined. The fusion zones 31 and 32 appear to be separated in the cross-sectional view, but are connected along the outer periphery of the precious metal tip 15.
[0019] A spark gap 17 is formed between the noble metal tip 15 and the noble metal tip 16. Discharge occurs between the noble metal tip 15 and the noble metal tip 16 in the spark gap 17, and a spark is generated.
[0020] Both the noble metal tips 15 and 16 are formed in a cylindrical shape. For example, the noble metal tip 15 has an outer diameter A of 1.0 mm and a height B of 1.5 mm. The noble metal tip 16 has an outer diameter C of 1.0 mm and a height D of 0.5 mm.
[0021] 1, as is well known, a central shaft 18 and a terminal portion 19 are electrically connected to the upper portion of the center electrode 13. An external circuit that applies a high voltage for generating sparks is connected to the terminal portion 19. In addition, a gasket 20 used for mounting to an internal combustion engine is provided on the upper end portion of the threaded portion 11a of the housing 11.
[0022] The precious metal tips 15, 16 are formed of an IrRh alloy based on Ir (iridium), which has a high melting point and excellent wear resistance, and containing Rh (rhodium) to suppress the high-temperature volatility of Ir. The IrRh alloy can suppress the oxidation and volatilization of Ir from grain boundaries in high-temperature air or oxidizing atmosphere. An IrRh alloy containing preferably 5 to 50 wt% Rh, and more preferably 5 to 30 wt% Rh, can suppress the oxidation and volatilization of Ir from grain boundaries in high-temperature air or oxidizing atmosphere. In the IrRh alloy, the components other than Rh and Ta are Ir.
[0023] The state in which the noble metal tip 15 and the front end portion 13a serving as the center electrode base material are joined will now be described with reference to Fig. 3. In order to examine the optimum values of the components of the fusion zones 31 and 32, the components of the fusion zones 31 and 32 at measurement points were measured.
[0024] The molten zone height L1 of the molten zone 31 is defined. The molten zone height L1 is the vertical length between the highest and lowest points of the molten zone 31. A measurement line L1 / 2 is set at the vertical center position of the molten zone height L1. Next, the molten zone length A1 of the molten zone 31 is defined. The molten zone length A1 is the horizontal length of the molten zone 31 at the measurement line L1 / 2. On the measurement line L1 / 2, two points that divide the molten zone length A1 into thirds are set as measurement points P11 and P12.
[0025] Similarly, the molten part height L2 is defined for the molten part 32. The molten part height L2 is the vertical length between the highest and lowest points of the molten part 32. A measurement line L2 / 2 is set at the vertical center position of the molten part height L2. Next, the molten part length A2 for the molten part 32 is defined. The molten part length A2 is the horizontal length of the molten part 32 at the measurement line L2 / 2. On the measurement line L2 / 2, two points that divide the molten part length A2 into thirds are set as measurement points P21 and P22.
[0026] FIG. 4 shows the results of measuring the components of the fusion zones 31, 32 at the measurement points P11, P11 defined as above and also of carrying out an engine durability test.
[0027] For the engine durability test, a test spark plug 10 was prepared under the following conditions and used. Thread diameter: M12 Screw length: 26.5mm HEX (hexagonal facet): 14mm Precious metal tip diameter: φ0.3mm, φ0.8mm Precious metal ratio Rh: 10wt%, Ta: 0~1.2wt%, Ir: remainder Welded part length: 0.2A (bonding rate 36%)
[0028] The engine durability test was performed under the following test conditions: a 2000cc 4-cylinder engine was fitted with a test spark plug 10, and the engine was idled for 1 minute, then the engine was kept at 5600 r / min for 1 minute (one cycle), and the engine was checked for the presence or absence of the precious metal tip 15 falling off. The test was performed for 100 hours, 150 hours, and 200 hours. 100 hours corresponds to 100,000 km of driving, 150 hours corresponds to 150,000 km of driving, and 200 hours corresponds to 200,000 km of driving.
[0029] As shown in Fig. 4, if the Vickers hardness of the fusion zones 31, 32 is 330 or more, no falling off of the precious metal tip 15 was observed in the engine durability test up to 100 hours. If the Vickers hardness of the fusion zones 31, 32 is 350 or more, no falling off of the precious metal tip 15 was observed in the engine durability test up to 150 hours. If the Vickers hardness of the fusion zones 31, 32 is 400 or more, no falling off of the precious metal tip 15 was observed in the engine durability test up to 200 hours.
[0030] The average hardness Y of the fusion zones 31, 32 measured by Vickers hardness is expressed by formula (f1) using a component ratio α measured by mass percent concentration of Ir and a component ratio β measured by mass percent concentration of Ta. Y=113.6+5.1α+62.9β (f1)
[0031] FIG. 5 shows the relationship between the component ratio α based on the mass percent concentration of Ir, the component ratio β based on the mass percent concentration of Ta, and the average hardness Y based on the Vickers hardness of the fusion zones 31 and 32 in the form of a hardness contour map. Region S1 is a region where the average hardness Y is 250 to 300 HV. Region S2 is a region where the average hardness Y is 300 to 350 HV. Region S3 is a region where the average hardness Y is 350 to 400 HV. Region S4 is a region where the average hardness Y is 400 to 450 HV. Region S5 is a region where the average hardness Y is 450 to 500 HV. Region S6 is a region where the average hardness Y is 450 to 500 HV.
[0032] The average hardness Y of the fusion zones 31, 32 based on Vickers hardness is expressed by formula (f1) using the component ratio α based on the mass percentage concentration of Ir and the component ratio β based on the mass percentage concentration of Ta, so the average hardness Y of the fusion zones 31, 32 based on Vickers hardness can be adjusted by adjusting the components of the precious metal chip 15.
[0033] By including Ir and Ta in the fusion parts 31, 32 so that the average Vickers hardness of the fusion parts 31, 32 is Y≧330, the durability of the spark plug 10 can be improved. Furthermore, by including Ir and Ta in the fusion parts 31, 32 so that the average Vickers hardness of the fusion parts 31, 32 is Y≧350, the durability of the spark plug 10 can be further improved.
[0034] From the viewpoint of reliability, it is preferable that the fusion zone heights L1, L2 are 0.2 mm or more. On this premise, the lengths A1, A2 of the fusion zones 31, 32 were examined. Test spark plugs were produced in which the total value of the lengths A1, A2 of the fusion zones 31, 32 was changed, and engine durability tests were performed. The test spark plugs 10 were produced under the following conditions. Thread diameter: M12 Screw length: 26.5mm HEX (hexagonal facet): 14mm Precious metal tip diameter: φ0.3mm, φ0.8mm Precious metal ratio Ir: 30wt%, Ta: 1.2wt%, Ni alloy: balance Hardness of fusion zone: 330HV
[0035] The engine durability test was performed under the following conditions: the test spark plug 10 was attached to a 2000cc 4-cylinder engine, and the engine was idled for 1 minute, then the engine was run at 5600 r / min for 1 minute (one cycle), and the engine was checked for the presence or absence of the precious metal tip 15. The presence or absence of the precious metal tip 15 was checked for 100 hours (equivalent to a run of 100,000 km).
[0036] 6, the total value of lengths A1, A2 of fusion zones 31, 32 is preferably 0.2 times (bonding rate 36%) or more the outer diameter A of precious metal tip 15. Similar results were obtained with precious metal ratios other than those used in this experiment.
[0037] The fusion parts 31 and 32 described with reference to Fig. 3 may be connected to each other to form an integrated fusion part. An example of an integrated fusion part will be described with reference to Fig. 7.
[0038] A molten zone height L3 in the molten zone 33 is defined. The molten zone height L3 is the vertical length between the highest point and the lowest point of the molten zone 33. A measurement line L3 / 2 is set at the vertical center position of the molten zone height L3. Next, a molten zone length A3 in the molten zone 33 is defined. The molten zone length A3 is the horizontal length of the molten zone 33 at the measurement line L3 / 2. At the measurement line L3 / 2, four points that divide the molten zone length A3 into five equal parts are set as measurement points P31, P32, P33, and P34. At the measurement points P31, P32, P33, and P34 set in this way, the components of the molten zone 33 may be measured and an engine durability test may be performed.
[0039] In the above description, the noble metal tips 15, 16 are formed of an IrRh alloy containing Rh (rhodium) based on Ir (iridium) having a high melting point and excellent wear resistance in order to suppress high-temperature volatility of Ir. The metal tips 15, 16 may be formed of an IrPt alloy containing Pt (platinum) based on Ir (iridium) having a high melting point and excellent wear resistance in order to suppress high-temperature volatility of Ir. The IrPt alloy can suppress the oxidation and volatilization of Ir from grain boundaries in high-temperature air or oxidizing atmosphere. The IrPt alloy preferably contains 5 to 50 wt% Pt, and more preferably contains 5 to 30 wt% Pt, can suppress the oxidation and volatilization of Ir from grain boundaries in high-temperature air or oxidizing atmosphere. In the IrPt alloy, the components other than Pt and Ta are Ir.
[0040] FIG. 8 shows the results of measuring the components of the fusion zones 31, 32 at the measurement points P11, P11 defined as above and also of carrying out an engine durability test.
[0041] For the engine durability test, a test spark plug 10 was prepared under the following conditions and used. Thread diameter: M12 Screw length: 26.5mm HEX (hexagonal facet): 14mm Precious metal tip diameter: φ0.3mm, φ0.8mm Precious metal ratio Pt: 10wt%, Ta: 0~1.2wt%, Ir: remainder Welded part length: 0.2A (bonding rate 36%)
[0042] The engine durability test was performed under the following test conditions: a 2000cc 4-cylinder engine was fitted with a test spark plug 10, and the engine was idled for 1 minute, then the engine was kept at 5600 r / min for 1 minute (one cycle), and the engine was checked for the presence or absence of the precious metal tip 15 falling off. The test was performed for 100 hours, 150 hours, and 200 hours. 100 hours corresponds to 100,000 km of driving, 150 hours corresponds to 150,000 km of driving, and 200 hours corresponds to 200,000 km of driving.
[0043] As shown in FIG. 8, if the Vickers hardness of the fusion zones 31, 32 is 310 or more, no falling off of the precious metal tip 15 was observed in the engine durability test up to 100 hours. If the Vickers hardness of the fusion zones 31, 32 is 340 or more, no falling off of the precious metal tip 15 was observed in the engine durability test up to 150 hours. If the Vickers hardness of the fusion zones 31, 32 is 360 or more, no falling off of the precious metal tip 15 was observed in the engine durability test up to 200 hours. If the Vickers hardness of the fusion zones 31, 32 is 410 or more, no falling off of the precious metal tip 15 was observed in the engine durability test up to 250 hours.
[0044] The average hardness Y of the fusion zones 31, 32 measured by Vickers hardness is expressed by formula (f2) using a component ratio α measured by mass percent concentration of Ir and a component ratio β measured by mass percent concentration of Ta. Y=111.1+4.8α+91.7β (f2)
[0045] 9 shows the relationship between the component ratio α in terms of the mass percent concentration of Ir, the component ratio β in terms of the mass percent concentration of Ta, and the average hardness Y in terms of Vickers hardness of the fusion zones 31, 32 in the form of a hardness contour map. Region S1A is a region where the average hardness Y is 250 to 300 HV. Region S2A is a region where the average hardness Y is 300 to 360 HV. Region S3A is a region where the average hardness Y is 360 to 400 HV. Region S4A is a region where the average hardness Y is 400 to 440 HV. Region S5A is a region where the average hardness Y is 440 to 560 HV.
[0046] The average hardness Y of the fusion zones 31, 32 based on Vickers hardness is expressed by formula (f2) using the component ratio α based on the mass percentage concentration of Ir and the component ratio β based on the mass percentage concentration of Ta, so the average hardness Y of the fusion zones 31, 32 based on Vickers hardness can be adjusted by adjusting the components of the precious metal chip 15.
[0047] The fusion parts 31, 32 contain Ir and Ta so that the average Vickers hardness of the fusion parts 31, 32 is Y≧310, thereby improving the durability of the spark plug 10. Furthermore, the fusion parts 31, 32 contain Ir and Ta so that the average Vickers hardness of the fusion parts 31, 32 is Y≧340, thereby improving the durability of the spark plug 10. Furthermore, the fusion parts 31, 32 contain Ir and Ta so that the average Vickers hardness of the fusion parts 31, 32 is Y≧360, thereby improving the durability of the spark plug 10. Furthermore, the fusion parts 31, 32 contain Ir and Ta so that the average Vickers hardness of the fusion parts 31, 32 is Y≧380, thereby improving the durability of the spark plug 10. Furthermore, the fusion zones 31, 32 contain Ir and Ta so that the average Vickers hardness Y of the fusion zones 31, 32 satisfies Y≧410, thereby making it possible to further improve the durability of the spark plug 10.
[0048] From the viewpoint of reliability, it is preferable that the fusion zone heights L1, L2 are 0.2 mm or more. On this premise, the lengths A1, A2 of the fusion zones 31, 32 were examined. Test spark plugs were produced in which the total value of the lengths A1, A2 of the fusion zones 31, 32 was changed, and engine durability tests were performed. The test spark plugs 10 were produced under the following conditions. Thread diameter: M12 Screw length: 26.5mm HEX (hexagonal facet): 14mm Precious metal tip diameter: φ0.3mm, φ0.8mm Precious metal ratio Ir: 30wt%, Pt: 1.2wt%, Ni alloy: balance Hardness of fusion zone: 330HV
[0049] The engine durability test was performed under the following conditions: the test spark plug 10 was attached to a 2000cc 4-cylinder engine, and the engine was idled for 1 minute, then the engine was run at 5600 r / min for 1 minute (one cycle), and the engine was checked for the presence or absence of the precious metal tip 15. The presence or absence of the precious metal tip 15 was checked for 100 hours (equivalent to a run of 100,000 km).
[0050] 10, the total value of lengths A1, A2 of fusion zones 31, 32 is preferably 0.2 times (bonding rate 36%) or more the outer diameter A of precious metal tip 15. Similar results were obtained with precious metal ratios other than those used in this experiment.
[0051] The present embodiment has been described above with reference to specific examples. However, the present disclosure is not limited to these specific examples. Any design modifications made by a person skilled in the art to these specific examples are also included within the scope of the present disclosure as long as they have the features of the present disclosure. The elements of each of the above-mentioned specific examples and their arrangements, conditions, shapes, etc. are not limited to those exemplified and can be changed as appropriate. The combination of each of the elements of each of the above-mentioned specific examples can be changed as appropriate as long as no technical contradiction occurs. [Explanation of symbols]
[0052] 10: Spark plug 11: Housing 11a: Threaded part 11b: Upper end 12: Insulator 13: Center electrode 13a:Tip 14: Ground electrode 14a: Tip 15: Precious metal chip 16: Precious metal chip 17: Spark Gap 18: Central axis 19:Terminal section 20: Gasket 31, 32: Welding part
Claims
1. A spark plug, A discharge unit that discharges when a voltage is applied to the discharge unit; In the discharge portion, the central electrode base material (13a) and the precious metal tip (15) are fused and joined together, and fused portions (31, 32) are formed at the fused and joined portions, The center electrode base material contains Ni, Cr, and Fe, The noble metal tip includes Ir, Rh, and Ta, The average hardness Y of the fusion zone in terms of Vickers hardness is expressed by the formula (f1) using a component ratio α in terms of the mass percent concentration of Ir and a component ratio β in terms of the mass percent concentration of Ta, Y=113.6+5.1α+62.9β (f1) The fusion zone contains Ir and Ta so that Y≧450.
2. A spark plug, A discharge unit that discharges when a voltage is applied to the discharge unit; In the discharge portion, the central electrode base material (13a) and the precious metal tip (15) are fused and joined together, and fused portions (31, 32) are formed at the fused and joined portions, The center electrode base material contains Ni, Cr, and Fe, The noble metal tip includes Ir, Pt, and Ta, The average hardness Y of the fusion zone in terms of Vickers hardness is expressed by formula (f2) using a component ratio α in terms of mass percent concentration of Ir and a component ratio β in terms of mass percent concentration of Ta, Y=111.1+4.8α+91.7β (f2) The fusion zone contains Ir and Ta so that Y≧410.
Citation Information
Patent Citations
Spark plug and its manufacturing method
JP2003197347A
spark plug
JP2009531813A
Spark plug
JP2011253826A
Spark plug electrode and spark plug
JP2019110114A
Spark plug
JP2020119800A